Mendiagnosa Penyakit Lambung Pada Sistem Pakar Berbasis Web Menggunakan Metode Fuzzy Mamdani - Anggrek, Denise Valeria; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 1 (2023): JELIKU Volume 12 No 1, August 2023DO - 10.24843/JLK.2023.v12.i01.p02, 2023)
Expert system is the one of Artificial Intelligence (AI) . One type of expert system in the health sector is an expert system for diagnosing the stomach diseases which is based on symptoms or complaints of experience by the patient. The stomach diseases has several types, there are Gastritis, Dyspepsia, Gastroesophageal Reflex Disease (GERD), Stomach Cancer, Stomach Tumor. The right solution to overcome these problems is to maintain health and need a system to diagnose the symptoms of stomach disease in human to resolve the stomach diseases in the right time. An Expert Systems of stomach diseases diagnose used the fuzzy mamdani method.   Keywords : Expert System, Fuzzy Method, Mamdani Artificial Intelligence, Stomach Diseases, Diagnose